2019
DOI: 10.2298/jmmb181214029b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platinum-aluminide coating features on high-temperature fatigue life of nickel-based superalloy Rene®80

Abstract: Low cycle fatigue is the most important failure mode in Aviation/Industrial engine rotary turbine parts. In this paper, the influence of Pt-aluminide coating parameters on high temperature low cycle fatigue behavior of superalloy Rene?80 which is used to manufacture turbine blades, has been investigated. For this purpose, initial platinum layers of different thicknesses (2?m and 8?m) were coated on fatigue specimens. Then the aluminizing process was performed with two conditions of low temperature-high activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Results of fatigue test on the uncoated Rene ® 80 specimens at 871 °C and total strain range of 0.8% have been reported by us in the previous study (Barjesteh et al, 2019a). The results of the previous study are shown in Table 3.…”
Section: Cyclic Stress-strain Behavior Of Uncoated Specimenssupporting
confidence: 56%
See 4 more Smart Citations
“…Results of fatigue test on the uncoated Rene ® 80 specimens at 871 °C and total strain range of 0.8% have been reported by us in the previous study (Barjesteh et al, 2019a). The results of the previous study are shown in Table 3.…”
Section: Cyclic Stress-strain Behavior Of Uncoated Specimenssupporting
confidence: 56%
“…Diffusion coatings exhibit low ductility below the DBTT, whereas above this temperature ductility increases (Bose, 2007). Decreased low cycle fatigue (LCF) properties of Rene ® 80 alloy following the application of CODEP-B, a plain aluminide coating, at the total strain range 1.2%, and an increase in this property at total strains below 0.8% at 871 °C have been reported by Rahmani and Nategh (2008b), while applying of Pt-Al coating on this superalloy reduced low cycle fatigue property at the same total strain and temperature conditions (Barjesteh et al, 2019a).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations